A single center retrospective cohort study comparing low-molecular-weight heparins to direct oral anticoagulants for the treatment of venous thromboembolism in patients with cancer – A real world experience. (June 2019) - Phelps, Megan K; Wiczer, Tracy E; Erdeljac, H Paige; Van Deusen, Kelsey R; Porter, Kyle; Philips, Gary; Wang, Tzu-Fei
Introduction: Low-molecular-weight heparins are the standard treatment for cancer-associated thrombosis. Recently, direct oral anticoagulants are a new option for thrombosis treatment; however, data supporting the use of direct oral anticoagulants for cancer-associated thrombosis are limited. Objectives: The primary objective of this study was to determine the rate of recurrent cancer-associated thrombosis and major bleeding within 6 months of starting either low-molecular-weight heparin or direct oral anticoagulant for treatment of cancer-associated thrombosis. Secondary objectives were to determine the rates of clinically relevant-non-major bleeding and all-cause mortality. Patients/methods: This is a retrospective cohort study including adults with cancer-associated thrombosis treated with low-molecular-weight heparin or direct oral anticoagulant between 2010 and 2016 at the Ohio State University. Medical records were reviewed for 6 months after initiation of anticoagulation or until the occurrence of recurrent cancer-associated thrombosis, major bleeding, cessation of anticoagulation of interest, or death, whichever occurred first. Results: Four hundred and eighty patients were included (290 low-molecular-weight heparin and 190 direct oral anticoagulant). Patients treated with direct oral anticoagulant were found to carry "lower risk" features including cancer with lower VTE risk and lower rate of metastatic disease. After adjustment for baseline differences, there was no significant difference in the rate of recurrent cancer-associated thrombosis (7.2% low-molecular-weight heparin vs 6.3% direct oral anticoagulant, p = 0.71) or major bleeding (7.6% low-molecular-weight heparin vs 2.6% direct oral anticoagulant, p = 0.08). Conclusions: Our study demonstrates that in a select population of cancer patients with VTE, direct oral anticoagulant use can be as effective and safe compared to the standard therapy with low-molecular-weight heparin.